Studi Fenomenologi: Kebijakan Pemerintah dalam Pemberian Jaminan Pemeliharaan Kesehatan bagi Masyarakat Miskin yang Mengalami Masalah Kesehatan Jiwa - Achir Yani S. Hamid; Mustikasari Mustikasari; Ria Utami Panjaitan; Purwadi Purwadi (Jurnal Ners, 2011)
Introduction: Limited of government’s budget for psychiatric patients has contributed to the expenses should be paid from out of pocket of the poor patients. The purpose of this research was to describe the Government policy on health social security insurance for the poor people experiencing psychiatric problems in DKI Jakarta.Methods: Qualitative research method was used with phenomenology approach to identify and describe the themes relevant to government public policy in providing health insurance for poor people with mental health problems. An in-depth interview and focus group discussion were used to collect data from different informants: service user, healthcare provider, local government policy maker. The qualitative data was analyzed using content analysis.Results: The study revealed the following themes: from user perspective (understanding of psychiatric disorder, social security network/JPKM, right and obligation, the advantage and barrier for receiving services, expectation from care provider, social support and expected future direction); from the perspective of healthcare provider (understanding of social security network/JPKM, types of provided health services, recording and reporting, referral system, cost, and the criteria of poor people), from local government and health office perspective (understanding of JPKM for poor family, scope of work, working procedure, recording and reporting, cost, accountability, poor people criteria, the relationship between central Government policy with local government policy.Conclusion: The finding of this study recommend the need for leveling socialization of JPKM, the budget transparences, improving the healthcare providers’ knowledge on the mental health psychiatric problems and its needs.